Analysis of antibody clonotype by affinity immunoblotting - Kurien, Biji T. (Methods Mol Biol, 2015)
A sensitive and specific method to analyze specific antibody clonotype changes in a lupus patient who developed autoantibodies to the Ro 60 autoantigen under observation is described. Patient sera collected over several years were separated by flatbed isoelectric focusing (IEF) and analyzed by affinity immunoblotting utilizing Ro 60-coated nitrocellulose membrane. When the Ro 60-coated nitrocellulose was laid over the surface of the IEF gel, the antibodies present on the surface of the acrylamide gel bound the Ro antigen on the nitrocellulose. Tween-20 was used to prevent non-specific binding. The bound IgG clonotypes were detected using alkaline phosphatase conjugated anti-IgG. The patient’s sera demonstrated an oligoclonal response to the Ro 60 autoantigen that increased in complexity and affinity over time.